2017
DOI: 10.1007/s10529-017-2486-z
|View full text |Cite
|
Sign up to set email alerts
|

Long-term H2 photoproduction from starch by co-culture of Clostridium butyricum and Rhodobacter sphaeroides in a repeated batch process

Abstract: The prolonged repeated batch photofermentation of starch by co-culture C. butyricum and R. sphaeroides provided efficient H production without accumulation of organic acids under conditions of Clostridia limitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The co-culture system operates in harmony, ensuring process stability and superior performance compared to monocultures. It has successfully addressed the limitations of axenic cultures, offering economic and methodological advantages over enzymatically hydrolyzed cellulose by eliminating the need for reductants during the fermentation process [217]. It is worth noting that the co-fermentation of seaweeds with other feedstocks is a relatively unexplored area that demands in-depth research and exploration.…”
Section: Co-fermentationmentioning
confidence: 99%
“…The co-culture system operates in harmony, ensuring process stability and superior performance compared to monocultures. It has successfully addressed the limitations of axenic cultures, offering economic and methodological advantages over enzymatically hydrolyzed cellulose by eliminating the need for reductants during the fermentation process [217]. It is worth noting that the co-fermentation of seaweeds with other feedstocks is a relatively unexplored area that demands in-depth research and exploration.…”
Section: Co-fermentationmentioning
confidence: 99%
“…Moreover, several studies on H 2 production by photosynthetic bacteria and bacteria co-cultures have been reported [50][51][52]. Kao [50][51][52].…”
Section: Manufacturing Of Biomoleculesmentioning
confidence: 99%
“…Moreover, several studies on H 2 production by photosynthetic bacteria and bacteria co-cultures have been reported [50][51][52]. Kao [50][51][52]. In the work of Hitit et al, the dark-and photo-fermentation processes were simultaneously carried out in a single-stage process by using co-cultures of Clostridium butyricum and Rhodopseudomonas palustris in order to enhance H 2 production [53].…”
Section: Manufacturing Of Biomoleculesmentioning
confidence: 99%
“…Further, they found hydrogen production by C. butyricum in co-culture with Rhodobacter sphaeroides N7 was retarded as compared to the mono-culture after 3 days (Laurinavichene and Tsygankov, 2015) and confirmed that a high yeast extract concentration (160-320 mg/L) enhanced reliable H 2 production . They used a repeated batch photofermentation utilizing starch with coculture of C. butyricum and R. sphaeroides N7 over 15 months to obtain efficient H 2 production with an average H 2 yield of 5.2 mol/mol glucose with no accumulation of organic acids in the presence of Clostridia (Laurinavichene et al, 2018). The highest hydrogen yield of 6.4 ± 1.3 mol/mol glucose was achieved upon optimization of the culture conditions using response surface methodology in the co-culture system of C. butyricum NRRLB1024 and Rhodospeudomonas palustris GCA009 (Hitit et al, 2017a).…”
Section: Hydrogen Productionmentioning
confidence: 99%